Shareholder capitalism, normative smokescreens and the angry, insecure knowledge worker - Cushen, Jean (Trinity College (Dublin, Ireland). Department of Sociology, 2010)
This thesis is rooted within the discipline of industrial sociology. It makes connections between workplace structures and subjectivities within a contemporary, stock market listed, high technology and knowledge intensive organisation. This thesis arose from the largely incompatible conclusions offered in the literatures that claim to define the employment experience in such workplaces. This thesis is based on a six month, mixed methods, critical realist, ethnography. It was undertaken within an Irish based subsidiary of a multi-national corporation. I secured full-time access to this organisation from June 2007 to November 2007 inclusive. During this time I analysed a wide range of documentation, conducted seventy five interviews and attended twenty five meetings. Critical realism is particularly suitable for this study as it focuses on the interplay between structures and subjectivities. Critical realism is also suitable for ethnographic research as the realist ontology involves contextually situating micro-level occurrences within a broader plurality of structures. The primary focus of this thesis is to explore and connect the structures that shape a successful, market listed, knowledge intensive organisation. In doing so, this thesis demonstrates the value of undertaking a holistic analysis of the myriad of structures shaping the work environment. Within the case study organisation, subjective orientations were informed by both the content within structures and the contradictions between them. The secondary focus is to explore the connection between these structures and the subjective orientation of different groups of actors. In doing so this thesis demonstrates the continued analytical richness of actor categories such as ‘capital’, ‘management’ and ‘labour’. Within the case study organisation, these specific categories were well recognised by all level of stakeholders and had real implications.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin